PENGEMBANGAN SMART VILLAGE MENUJU EKONOMI MASYARAKAT DESA MANDIRI DI DESA WAY HUWI KECAMATAN JATI AGUNG KABUPATEN LAMPUNG SELATAN - Tiara Nirmala; Arivina Ratih; Moneyzar Usman; Didik Kurniawan (Yayasan Education and Social Center, 2022)
Way Huwi Village is located in Kec. Jati Agung, South Lampung Regency, Lampung Province. This village has an area of ??500.32 hectares with a population of 4063 people consisting of 1051 families. Potential Natural Resources are agriculture and also the trade sector. Based on its geographical location, Way Huwi Village is in a strategic area where the entire area already has a PLN electricity network and is covered by a cellular telephone network and is close to the ITERA campus area, so that the community is familiar with the use of information and communication technology. If referring to Law Number 6 of 2014 concerning Villages, it becomes a very big opportunity for every village in Indonesia, especially Way Huwi Village to be able to develop every potential it has independently as needed in order to realize community welfare. There are several obstacles that Way Huwi Village is still facing to get to Smart Village, one of which is, the current community's economic activities are mostly carried out offline. On the other hand, Way Huwi Village has several sources of economic potential, namely BUMDES which should by looking at the readiness of existing technology, MSMEs partnering with BUMDES can utilize Information Technology to create MSME Mapping Information Systems and conduct marketing (e-marketing).